A coronavirus assembly inhibitor that targets the viral membrane protein - Laporte, Manon; Jochmans, Dirk; Bardiot, Dorothée; Desmarets, Lowiese; Debski-Antoniak, Oliver J.; Mizzon, Giulia; Abdelnabi, Rana; Leyssen, Pieter; Chiu, Winston; Zhang, Zhikuan; Nomura, Norimichi; Boland, Sandro; et al. (Nature, 2025)
The coronavirus membrane protein (M) is the main organizer of coronavirus assembly1-3. Here, we report on an M-targeting molecule, CIM-834, that blocks the assembly of SARS-CoV-2. CIM-834 was obtained through high-throughput phenotypic antiviral screening followed by medicinal-chemistry efforts and target elucidation. CIM-834 inhibits the replication of SARS-CoV-2 (including a broad panel of variants) and SARS-CoV. In SCID mice and Syrian hamsters intranasally infected with SARS-CoV-2, oral treatment reduced lung viral titres to nearly undetectable levels, even (as shown in mice) when treatment was delayed until 24 h before the end point. Treatment of infected hamsters prevented transmission to untreated sentinels. Transmission electron microscopy studies show that virion assembly is completely absent in cells treated with CIM-834. Single-particle cryo-electron microscopy reveals that CIM-834 binds and stabilizes the M protein in its short form, thereby preventing the conformational switch to the long form, which is required for successful particle assembly. In conclusion, we have discovered a new druggable target in the replication cycle of coronaviruses and a small molecule that potently inhibits it.